MENGHITUNG ZAKAT PERUSAHAAN (Studi Kasus pada PT. Asuransi Takaful, BSM, BPRS, Dompet Dhuafa, BMT dan Pos Keadilan Peduli Umat) - Sofyan S. Harahap; Muh. Yusuf (Media Riset Akuntansi, Auditing & Informasi, 2002)
Zakat is a part of a personal muslim responsibility, it is the third of uarkanul Islam". The development of business entity affects the map, types, and characteristics of business, then affects also the map of zakat dues. During the period of the Prophet Muhammad, the type of business was different from the type of business today. There is no a specific Quranic ayah or hadist determines the company zakat rate. Mostly the rate of zakat based on economic activities rather than on an entity. In that case we have a problem how to calculate a company zakat. This study will discuss how some companies which daim as a syariah companies calculate their entity zakat. This issue becomes more important after the government implement the Zakat Act (UU) No 38/ 1998.Keywords: Islamic Fiqih, Zakat, Islamic accounting, Islamic organaization.